2016
DOI: 10.1021/acs.analchem.5b03490
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Determination of Pyocyanin and 1-Hydroxyphenazine as Potential Biomarkers of Pseudomonas aeruginosa Infections

Abstract: A novel immunochemical approach to diagnose Pseudomonas aeruginosa infections is reported, which is based on the quantification of relevant and specific virulence factors secreted by this microorganism. Specific antibodies have been raised using hapten PC1 (a 1:1 mixture of 9-hydroxy- and 6-hydroxy-phenazine-2-carobxylic acids), designed to recognize 1-hydroxyphenazine (1-OHphz), which is the main metabolite of pyocyanin (PYO). PYO is one of the most important virulence factors produced by nearly all P. aerugi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…The antimicrobial activity of OBPs could also be exerted by scavenging other compounds produced by pathogenic microorganisms, with physico-chemical properties and/or molecular masses comparable to those of the ligands of these proteins. As an example, the binding tests for pyocyanin showed that it can be significantly scavenged by submillimolar levels of bovine and porcine OBPs at concentration levels higher than 5 μM, being this concentration value comparable to those active in vivo during PA infections [39, 40 and 41]. The binding capacity of OBPs against pyocyanin is an additional indication of the potential scavenging-based antimicrobial activity of the protein against PA. Further studies dealing with other bacterial and yeast toxins, as well as with diffusible bioactive compounds having molecular characteristics comparable to those of the OBP ligands, could corroborate the hypothesis that OBPs might exert an in vivo scavenging-based antimicrobial activity against a wide spectrum of pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity of OBPs could also be exerted by scavenging other compounds produced by pathogenic microorganisms, with physico-chemical properties and/or molecular masses comparable to those of the ligands of these proteins. As an example, the binding tests for pyocyanin showed that it can be significantly scavenged by submillimolar levels of bovine and porcine OBPs at concentration levels higher than 5 μM, being this concentration value comparable to those active in vivo during PA infections [39, 40 and 41]. The binding capacity of OBPs against pyocyanin is an additional indication of the potential scavenging-based antimicrobial activity of the protein against PA. Further studies dealing with other bacterial and yeast toxins, as well as with diffusible bioactive compounds having molecular characteristics comparable to those of the OBP ligands, could corroborate the hypothesis that OBPs might exert an in vivo scavenging-based antimicrobial activity against a wide spectrum of pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…PYO was obtained from Sigma-Aldrich Co. (St. Louis, MO), and 1-OHphz was synthesized following the procedures ( Vivian, 1956 ). The development of the anti-1-OHphz pAb As230 was described by Pastells et al. (2016) .…”
Section: Methodsmentioning
confidence: 99%
“…These methods, based on the specific interaction between an antigen and an antibody (Ab), are widely implemented in clinical laboratories ( Ma et al., 2019 ; Vatankhah et al., 2019 ; Zelini et al., 2019 ). Few years ago, we reported for the first time the development of polyclonal antibodies (pAbs) and microplate-based ELISA for 1-hydroxyphenazine (1-OHphz), the main metabolite of PYO, with an excellent detectability (IC 50 = 0.53 nM) ( Pastells et al., 2016 ). It has been reported that 1-OHphz also contributes to the virulence of P. aeruginosa .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Pastells and co-workers also published an immunochemical method for the quantification of PYO and its precursor 1-hydroxyphenazine (1-OHphz) in bacterial cultures and sputum samples [133]. PYO quantification could be done in less than 2 h after conversion to 1-OHphz under basic conditions, presenting a LOD of 0.6 nM.…”
Section: Immunochemical-based Techniquesmentioning
confidence: 99%